Students' Proficiency in Computational Thinking Through Constructivist Learning Theory - Angraini, Lilis Marina; Kania, Nia; Gürbüz, Ferit (EDUPEDIA Publisher, 2024)
This study aims to assess students' mathematical computational thinking skills in the Mathematics Education program, focusing on the constructivist learning paradigm. The primary objective of this study is to investigate the impact of the constructivist learning approach on enhancing students' mathematical computational thinking skills. This study is a qualitative descriptive research that investigates students' learning process in the context of acquiring computational understanding and applying computational principles in mathematics education. The study was conducted in the Department of Mathematics Education, focusing on students enrolled in the Algebraic Structure course during the academic year 2023/2024. A total of 34 students were included as the subjects of this investigation. The study's findings offer a valuable understanding of the efficacy of the constructivist learning paradigm in enhancing the mathematical computational thinking abilities of Mathematics Education students. The findings indicated that the students' overall mathematical computational thinking proficiency was satisfactory. Additionally, prior mathematical knowledge was found to have a differentiating effect on students' mathematical computational thinking ability, particularly within the context of constructivism learning theory.